Clever cat and the clown - Carlisle, Richard; Launchbury, Jane (Surrey : Templar Publishing, 2008)
This is one in a series of books which introduce children to the alphabet and help them take their first steps in reading and writing. Each Letterland character helps children with the sound and the shape of the letter as the child follows their adventures.
Keywords: Children's stories